Proposing an ontological shift from intervention to intravention in sport and exercise psychology. (January 2023) - Camiré, Martin
Abstract: Intervention research entails the measurement of change in a situation or individual after a modification has been imposed. In sport and exercise psychology, interventions have been implemented in a variety of situations (e.g., performance, doping, physical activity, mental health) for a variety of individuals (e.g., athletes, coaches, sedentary people). Despite their widespread use, accruing evidence indicates that interventions in sport and exercise psychology have had less than anticipated success in instigating change. While some scholars have pointed to the need to confront the methodological challenges of intervention implementation, others have called for the creation of viable alternative forms of inquiry that can complement intervention research. The purpose of the present article is to propose an ontological shift from intervention to intravention in sport and exercise psychology. This shift is undertaken through the deployment of Barad's (2007) agential realist ontology. The paper is divided into six sections. First, the concept of interaction is situated as it forms the basis for how interventions are conducted. Second, the Baradian ontology of agential realism is explained, along with key concepts. Third, intravention is positioned in relation to five guiding principles that delineate the progression for conducting intravention inquiries. Fourth, alternate meanings are proposed for behaviour, change, and knowledge. Fifth, examples are provided as to how intravention inquiries can be deployed in sport and exercise psychology. Sixth, concluding thoughts are offered. As an ontological becoming of interventions, intraventions are situated as open-ended approaches to inquiry that can help researchers derive alternate understandings of existence and can take the psychology of sport and exercise in exciting and affirmative directions. Highlights: An ontological shift, through the lens of agential realism, is proposed by introducing the concept of intravention. Intravention inquiries can help sport and exercise psychology inquirers attend to the relationality of existence. When enacted with care, intravention inquiries can help inquirers contemplate ethically responsible modes of existence.